Extent of caregiver burden among informal caregivers of persons with severe mental disorders in rural South Africa - Olindah Silaule; Nokuthula Nkosi; Fasloen Adams (James Cook University, 2023)
Introduction: Informal caregivers are the backbone of recovery for people with severe mental disorders in South Africa, particularly in rural areas where access to mental health services is limited. While their unique contribution and the subsequent burden arising from occupying the role of informal caregiver are acknowledged, there is limited evidence on the extent of the subjective and objective burdens among informal caregivers of people with severe mental disorders in rural areas. This article reports on a study that aimed to establish the extent of subjective and objective burdens among informal caregivers of people with severe mental disorders in rural South Africa. Methods: A descriptive quantitative cross-sectional design was used. Data were gathered through structured interviews with 170 informal caregivers of people with severe mental disorders attending an outpatient clinic at a rural hospital in South Africa. A structured questionnaire guided the interviews and included demographics and caregiving characteristic information. Montgomery, Gonyea and Hooyman's scale was used to assess objective and subjective burdens. Data was analysed descriptively using Stata v15. Results: The majority of the participants were female informal caregivers (83.5%) between the ages of 45 and 64 years (45.3%), and parents represented the largest proportion (45.3%) of caregivers. The global burden scores revealed that most informal caregivers reported moderate-to-severe objective burden and mild-to-moderate subjective burden. Significant associations with objective burden were established for age, gender and residence (p=0.025, p=0.034 and p=0.038, respectively), and subjective burden yielded significant associations with daily caregiving (p=0.012). Conclusion: Caring for people with severe mental disorders is associated with high levels of objective and subjective burdens. The present study highlights the need to integrate the assessment of burdens among informal caregivers of people with severe mental disorders in routine clinical practice. Additionally, the study urgently calls for the development of strategies to support informal caregivers to ensure successful community reintegration among people with severe mental disorders.